A Study on the Effectiveness of Infographics on Facebook for Grand Theft Auto V (GTAV) FiveM under the Apocalypse Universe FiveM Server - Pettanoo, Chanmetha; Tadamnuaychai, Montira (Siam Communication Review, 2025)
This research, titled "A Study on the Effectiveness of Infographics on Facebook for Grand Theft Auto V (GTAV) FiveM under the Apocalypse Universe FiveM Server," aims to evaluate the effectiveness of using infographics on the Facebook platform to enhance player awareness and engagement within the Apocalypse Universe FiveM server of GTAV. The study focuses on communication and promotion through Facebook Ads and the use of infographic content to attract new players and retain the existing player base. A quasi-experimental research method was employed to measure key performance indicators, including Follows, Reach, Impressions, and Engagement, using Facebook Ads Manager. The research findings indicate that the use of infographics in Facebook promotions resulted in a peak engagement of 91 interactions, with the highest ad impressions reaching 6,124 views. The implementation of Facebook Ads effectively expanded audience reach and contributed to an increase in new player acquisitions. Additionally, infographic-based content and activities significantly boosted player engagement within the server. Based on these findings, the researcher recommends continuous improvement and innovation in infographic content to maintain its appeal and relevance. Moreover, strategic planning of Facebook Ads campaigns should be carefully executed to optimize audience targeting and maximize effectiveness.